Kerangka Hadits Tarbawi Dalam Pendidikan Di Era Digital - Zulhamdan; Wisdar Hanum (Akademika: Jurnal Keagamaan dan Pendidikan, 2024)
This study aims to explain hadith related to Education in the Digital Era and explain according to current conditions and their implementation. This paper uses a Qualitative Descriptive Approach. Data collection techniques carried out by collecting data through literature from journals and books The results of the study showed that; Islamic education covers all ages and its implementation is based on the Morals exemplified by the Prophet Muhammad SAW